Penguatan Ekonomi Kreatif melalui Inovasi Produk UMKM Tarekli Guna Mendukung Program Wirausaha MBKM di Salama Kelurahan Na’e Kota Bima - Kartin Aprianti; Irma Mardian; Fanisyah Aulia Putri; Anna Nurhaliza; Nabila Islamiyah; Nurafrianingsih Nurafrianingsih; Faturrahman Faturrahman; Muhsin Muhsin (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
A weakness that is often faced by MSME players is product packaging which can be said to be ordinary or even unattractive. Packaging is one of the weaknesses of MSME products or competing with the products of large manufacturing companies. Several problems such as limited capital, market access and production volume mean that some MSME players do not consider packaging to be an important element of their business. To carry out MSME development in Tarekli MSMEs, we conducted a survey of Tarekli MSME players. Surveys were carried out to collect data and information, survey activities were carried out by visiting Tarekli MSME business locations and interviewing business owners directly with the results of determining the program that would be implemented and the time for implementing the work program. The results of the survey activities we carried out on MSMEs in Nae Village were to provide understanding and implementation of MSME product innovation in Nae Village by delivering material on product innovation and development, designing logos and brands, and providing product manufacturing training.